2019
DOI: 10.1002/pi.5758
|View full text |Cite
|
Sign up to set email alerts
|

Copolymerization modification: improving the processability and thermal properties of phthalonitrile resins with novel comonomers

Abstract: Two novel tetrahydrophthalic anhydride end‐capped imide compounds (THAN and THBN) with high thermal stability were synthesized to promote the curing reaction of 1,3‐bis(3,4‐dicyanophenoxy)benzene (3BOCN), and to study the effects of comonomer structure on the curing behavior and thermal performance of phthalonitrile resins. The curing behaviors of THAN/3BOCN and THBN/3BOCN blends with various molar ratios were investigated using rheological analysis and differential scanning calorimetry, suggesting a wide proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
1
7
0
Order By: Relevance
“…The thermal and thermal‐oxidative properties of Resins 1–4 were compared with the previously reported PN resins, as shown in Table . Among them, both A‐37 and Resins 1–4 are cured by radical promoted‐polymerization mechanism . It can be seen from the table that the Resins 1–4 and A‐37 have similar thermal properties.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The thermal and thermal‐oxidative properties of Resins 1–4 were compared with the previously reported PN resins, as shown in Table . Among them, both A‐37 and Resins 1–4 are cured by radical promoted‐polymerization mechanism . It can be seen from the table that the Resins 1–4 and A‐37 have similar thermal properties.…”
Section: Resultsmentioning
confidence: 99%
“…Our recent work has indicated that the alicyclic mono‐imide moiety (MAIM) could promote the polymerization and simplify the reaction path of PN [1,3‐bis(3,4‐dicyanophenoxy)benzene (3BOCN)] by the radical process . The product structures of radical promoted‐polymerization effect were mainly composed of isoindoline, minor phthalocyanine, which was different with traditional curing systems, since there was no triazine formed, and almost no nitrile left .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, researchers basically believe that CN polymerization mainly produces triazine, isoindole and phthalocyanine rings, [31][32][33][34][35][36][37][38][39][40][41][42] does not produce small molecules, and gives the polymerization mechanism of forming the three heterocycles. However, this does not explain the experimental results in this paper very well.…”
Section: The Possible Polymerization Mechanism Of 4-apnmentioning
confidence: 99%
“…So far, several methods have been developed to improve the above problems, including design of new phthalonitrile resin precursors and curing agents . For example, Yang et al prepared two novel tetrahydrophthalic anhydride end‐capped imide compounds to promote the curing reaction of 1,3‐bis(3,4‐dicyanophenoxy)benzene and also studied the effects of comonomer structure on the curing behavior and thermal performance of phthalonitrile resins. Wang et al prepared a novel high temperature vinylpyridine‐based phthalonitrile polymer; the monomer exhibited a lower melting point (92°C), which allowed for a longer processing window (146°C) and enhanced the processability without compromising the thermal and oxidative stabilities.…”
Section: Introductionmentioning
confidence: 99%